Данило Щербаківський про Першу південноросійську кустарну виставку: стратегія дій - Ходак, І. (Народна творчість та етнографія, 2007)
In 2006 was the 100th anniversary since the First South-Russian Handicraft Exhibition, which was organized in Kyiv in Art-Industrial Museum named after emperor Mykola the Second on the initiative of M. Bilyashivsky, had taken place. This exhibition played a great role in the creation of the unique collection of the folk art in Ukrainian capital. This article gives a description of the event itself and the reaction it had among press and cultural elite, and positive influence for future development of the handicraft and its popularization.